KEPENTINGAN PEMERINTAH INDONESIA DALAM MENJALIN HUBUNGAN DAGANG DENGAN TAIWAN - Shintia, Eni; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is a political economy study that describes the interests of Indonesia in establishing trade relations with Taiwan. The aim of this study is to determine Indonesia's interests in establishing trade relations with Taiwan. This study used qualitative research methods. This analysis is based on literature. The author used data from a collection of journals, books, documents, and the internet. The perspective that used is Liberalism, which according to this perspective assumes that humans are essentially non-conflict, willing to cooperate and rational beings. The level of analysis is Country-Nation, where the state is the dominant and most powerful actor in international interactions. The concept that used in this study is the concept of national interest, where this concept is the main pillar of foreign policy and international politics that are realistic because national interests determine the political actions of a country. The results of the research in the thesis are international cooperation, where the collaboration of this research occurs between Indonesia and Taiwan to meet the needs and interests of each country in the field of trade. The interest of the Indonesian Government in Establishing Trade Relations with Taiwan is to increase Indonesian cooperation in various sectors, such as Indonesia's exports which increased to USD 1.84 billion by 2018, Taiwan is very interested in investing in Indonesia amounting to 142 million US dollars, 7,200 Indonesian students in 2018 which are studying to Taiwan. Keywords: Nation Interest, One China Policy, International Relation